Integrated catalytic adsorption (ICA) steam gasification system for enhanced hydrogen production using palm kernel shell - Khan, Z. (2014)
This paper investigates the integrated catalytic adsorption (ICA) steam gasification of palm kernel shell for hydrogen rich gas production using pilot scale fluidized bed gasifier under atmospheric condition. The effect of temperature (600-750 C) and steam to biomass ratio (1.5-2.5 wt/wt) on hydrogen (H2) yield, product gas composition, gas yield, char yield, gasification and carbon conversion efficiency, and lower heating values are studied. The results show that H2 hydrogen composition of 82.11 vol is achieved at temperature of 675 C, and negligible carbon dioxide (CO 2) composition is observed at 600 C and 675 C at a constant steam to biomass ratio of 2.0 wt/wt. In addition, maximum H2 yield of 150 g/kg biomass is observed at 750 C and at steam to biomass ratio of 2.0 wt/wt. A good heating value of product gas which is 14.37 MJ/Nm3 is obtained at 600 C and steam to biomass ratio of 2.0 wt/wt. Temperature and steam to biomass ratio both enhanced H2 yield but temperature is the most influential factor. Utilization of adsorbent and catalyst produced higher H2 composition, yield and gas heating values as demonstrated by biomass catalytic steam gasification and steam gasification with in situ CO2 adsorbent. Â© 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserver.